Legal status of the judicial council of Montenegro as one of the determinants of the process of accession to the European Union. Theoretical and legal analysis - Nowak, Krystian (PRAWO i WIĘŹ, 2025)
By defining priorities and setting certain requirements for the independence of the judiciary, the EU contributes to strengthening democratic governance mechanisms. This is demonstrated by the requirement formulated by the EU to ensure the independence of the judiciary by delineating the proper position of the Judicial Council as a key element in the evolution of the relationship of an institutional nature between the political power and the body aiming to act as guarantor of the rule of law and controller of the powers of the supreme authority. The author of this article analyses the provisions of the Constitution and ordinary legislation that define the constitutional position of the Judicial Council within the framework of Montenegro's political system. It pays particular attention to the manner of election of the members of the council in the context of Montenegro's European aspirations. It focuses on showing the legal status of the council, draws attention to its composition and competences, as well as the status of the council's members, i.e. factors that are decisive for the actual establishment of the council's independence guarantees. In addition, the author attempts to answer the question whether Montenegrin normative solutions meet European standards in the adopted research scope. The Judicial Council of Montenegro is a specialised body with wide-ranging competences in the field of the judiciary, but requiring further changes in the composition of the council and the mode of election of its members.